A collaborative framework for enhancing graduate employability - Ferns, Sonia; Dawson, V.; Howitt, C. (2019)
© 2019 International Journal of Work-Integrated Learning. All rights reserved. Disruptive technologies, emerging global markets, and uncertain workforce requirements are driving the need for skilled graduates. This research developed a framework for collaboration between stakeholders to ensure work-ready graduates and sustained economic growth. A mixed-methods, multiple case study research design was deployed to gather data from graduates, employers, staff, students, and professional body representatives across three disciplines. The Australian course experience questionnaire generated 476 graduate responses and 1,175 comments. The graduate employability surveys collected responses from 88 graduates, 51 employers and 34 teaching staff. SPSS and Excel functions were used for quantitative data analysis and NVivo for thematic analysis. A cross-case analysis of the three case studies revealed consistency in stakeholder perceptions of domains perceived as important for graduate employability with collaborative partnerships emerging as integral to actualizing the domains. Findings from this research challenge conventional university approaches to brokering and maintaining partnerships and suggests a holistic engagement framework for stakeholders.